Dental health status assessment of TNI-AL bintara officers using DMFT index and Chief of Naval Staff Regulation: a descriptive study - Arifin, Kanisa Mirena; Irmaleny, Irmaleny; Sitam, Suhardjo; Setiawan, Krisnadi (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Military personnel belong to a high-risk group for the development of various pathological conditions in the oral cavity. Based on research, the experience of dental caries in the army population of several other countries was relatively high. The purpose of this study was to describe the assessment of the dental health status of Bintara Officer (the NCO) the Indonesian National Military-Naval Force (TNI-AL) using caries experience index. Methods: The descriptive method was used with primary data collection through the caries experience index (DMF-T) examination and assessment of the dental health status of the TNI-AL. A purposive sampling technique with a total of 40 members with inclusion criteria, ranked Bintara Officer, 10 years of service, male or female, was used. Exclusion criteria were those serving outside the city or abroad and not signing an informed consent form. The data was collected and analyzed descriptively using Microsoft Excel. Results: DMF-T index value was 3.7, included in the Stakes I category, which had a maximum number of DMF of 10 teeth: 25.0% in the very low category, 17.5% in the low category, 27.5% in the moderate category, 17.5% in the high category, and 12.5% in the very high category. The dental health status of the TNI-AL were 95.0% in the Stakes I category, 2.5% in the Stakes II category, 2.5% in the Stakes III category, and there were no subjects in the Stakes IV category. Conclusion: Assessment of the dental health status of bintara officer Indonesian National Military-Naval Force using DMFT index value was in the moderate category, and based on Perkasal the majority was included in the Stakes I category.KEYWORDS : Caries, DMF-T index, dentistry, TNI-AL dental health status